Hydrophobic surfactant-associated polypeptides: SP-C is a lipopeptide with two palmitoylated cysteine residues, whereas SP-B lacks covalently linked fatty acyl groups. - Curstedt, T (1990)
Pulmonary surfactant contains two hydrophobic polypeptides, SP-B and SP-C, with known amino acid sequences and with truncated subforms lacking the N-terminal residues. Treatment of SP-C with KOH releases fatty acids (palmitic acid to more than 85%) in molar ratios of 1.8-2.0 relative to the polypeptide. Furthermore, plasma-desorption mass spectrometry shows native SP-C of both the intact and truncated types to be monomers with masses about 500 units higher than those expected for the polypeptide chains. After treatment with KOH, trimethylamine, or dithioerythritol, the polypeptide masses are obtained. These results prove that native SP-C is a lipopeptide with two palmitoyl groups covalently linked to the polypeptide chain. The deacylation conditions, the presence of two cysteine residues in the polypeptide, and the absence of other possible attachment sites establish that the palmitoyl groups are thioester-linked to the two adjacent cysteine residues. In contrast, the major form of porcine SP-B is a dimer without fatty acid components. That SP-C is a true lipopeptide with covalently bound palmitoyl groups suggests possibilities for functional interactions. It gives a direct physical link between SP-C and surfactant phospholipid components. Long-chain acylation may constitute a means for association of proteins with membranes and could conceivably modulate the stability and biological activity of surfactant films.